Optimization of Corporate Tax Assessment to Increase State Income Revenue - Dadang Suwanda; Rahmat Heryat Furqon (Ekonomis: Journal of Economics and Business, 2023)
Tax is a huge potential source of revenue. A country's collection system, both Self Assessment and Official Assessment, greatly influences the increase in receipt of these government funds. Assessment test of corporate taxpayer compliance. The assessment test to obtain an objective and professional value for the object of appraisal following valuation standards and tax provisions so that state revenue can increase. The methodology used is based on the type of qualitative research, and the researcher can find an understanding or interpretation of a phenomenon that is happening. Descriptive qualitative research is using literature or literature study that focuses on explaining the research results obtained by the researchers by collecting in-depth interview data. The results of the study show that while business valuation is accomplished to determine the value of an object of appraisal objectively and professionally according to valuation standards and tax regulations on business continuity (going concern), including in business ownership interest, as well as transactions and everything that influences to corporate value.